Review of the book by Sh. M. Hapizova, S. M. Galbaseva «Avars Tsor: (Zakatala district) in the XVIII – the first half of the XX century (Essay of political and social history)» - Halaev, Z A (History, Archeology and Ethnography of the Caucasus, 2017)
null